Early antiretroviral therapy with raltegravir generates sustained reductions in HIV reservoirs but not lower T-cell activation levels. (15th May 2015) - Hey-Cunningham, William J.; Murray, John M.; Natarajan, Ven; Amin, Janaki; Moore, Cecilia L.; Emery, Sean; Cooper, David A.; Zaunders, John; Kelleher, Anthony D.; Koelsch, Kersten K.
Abstract : Objective: The initiation of antiretroviral therapy (ART) during primary infection may offer clinical benefits for HIV-infected individuals by reducing HIV DNA reservoir size and chronic T-cell activation. Current evidence for the advantages of early ART, however, are mostly derived from cross-sectional studies, with the long-term benefits yet to be ascertained. Design/methods: We conducted an open-label, nonrandomized study, monitoring for 3 years: plasma viral load (pVL), T-cell phenotypes, and peripheral CD4 + T-cell associated total, integrated and 2-long terminal repeat HIV DNA species. The study included 16 treatment-naive individuals initiating ART with raltegravir and Truvada during either primary (PHI, n  = 8) or chronic (CHI, n  = 8) HIV infection. Results: ART initiated during PHI compared with CHI generated significant reductions of peripheral CD4 + T-cell HIV DNA reservoirs that were sustained for 3 years of therapy. Median log10 HIV DNA copies/10 6 CD4 + T cells at the final visit: total; CHI = 3.23 > PHI = 2.72, P  < 0.01; integrated; CHI = 2.64 > PHI = 1.77, P  < 0.01. Similar trends were observed for pVL, however, did not reach significance: log10 HIV RNA copies/ml plasma at the final visit: CHI = 1.3 ≥ PHI = 0.39, P  = 0.08. Both cohorts displayed similar and elevated levels of CD38/HLA-DR coexpression on CD4 + and CD8 + T cells relative to uninfected healthy controls. Conclusion: The reduction in HIV DNA reservoirs generated by the early initiation of ART was sustained for 3 years of therapy. Although the PHI cohort trended to lower levels of pVL, and pVL was associated with CD8 + T-cell activation, no differences in T-cell activation were observed between the PHI and CHI groups. Abstract : Supplemental Digital Content is available in the text